Studi Perencanaan Struktur Atas Jembatan Semanding Tuban Dengan Menggunakan Struktur Rangka Baja - Dewi Hartini Caley; Retno Trimurtiningrum (Institut Teknologi Adhi Tama Surabaya, 2023)
This study aims to plan the superstructure of a steel frame bridge using K-truss type. The bridge that will be planned in this project has a span of 36 meters and the width of the bridge is 11 meters, located at stations 10+436.80 to stations 10+401 located at over the Semanding River and connects Tunah Village, Semanding District to the Village Prudara Kulon, Semanding District, Tuban. Design of steel structures using the Load and Resistance Factor Design (LRFD) approach. The planning of this bridge was assisted by Autocad software and SAP200 V22. The steel profile on the longitudinal girder is IWF 250 x 125 x 6 x 9 and for IWF transverse girders 1000 x 350 x 18 x 38. Longitudinal and transverse girders using a composite beam system. The main frame profile uses IWF 400 x 400 x 21 x 21, and IWF diagonal girders 400 x 400 x 21 x 21. Connections used on longitudinal girders and transversely, the connecting device is a bolt with a diameter of 20 mm and welding. Whereas the connection on the main frame is a gusset connection with the connecting device being a bolt 20 mm in diameter.